The Titanium-coated PEEK Cage Maintains Better Bone Fusion With the Endplate Than the PEEK Cage 6 Months After PLIF Surgery: A Multicenter, Prospective, Randomized Study. Issue 15 (1st August 2020) - Hasegawa, Tomohiko; Ushirozako, Hiroki; Shigeto, Ebata; Ohba, Tetsuro; Oba, Hiroki; Mukaiyama, Keijiro; Shimizu, Satoshi; Yamato, Yu; Ide, Koichiro; Shibata, Yosuke; Ojima, Toshiyuki; Takahashi, Jun; et al.
Abstract : Study Design: A multicenter, randomized, open-label, parallel-group trial. Objective: To investigate interbody bone fusion rates in titanium-coated polyetheretherketone (TiPEEK) and polyetheretherketone (PEEK) cages after posterior lumbar interbody fusion (PLIF) surgery. Summary of Background Data: Previous clinical studies have not revealed any significant difference in bone fusion rates between TiPEEK and PEEK cages. Methods: During one-level PLIF surgery, 149 patients (84 men, 65 women, mean age 67 yr) were randomly allocated to use either a TiPEEK cage (n = 69) or PEEK cage (n = 80). Blinded radiographic evaluations were performed using computed tomography and assessed by modified intention-to-treat analysis in 149 cases and per-protocol analysis in 143 cases who were followed for 12 months. Clinical outcomes were assessed using the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire and the Oswestry Disability Index. Results: The interbody union rate at 12 months after surgery was 45% owing to a very strict definition of bone fusion. The rates of bone fusion were significantly higher at 4 and 6 months after surgery in the TiPEEK group than in the PEEK group in the unadjusted modified intention-to-treat analysis and were significantly higher at 6 months in the unadjusted per-protocol analysis. Binary logistic regression analysis adjusted for sex, age, body mass index, bone mineral density, and surgical level showed that using a TiPEEK cage (odds ratio, 2.27; 95% confidence interval: 1.09–4.74; P  = 0.03) was independently associated with bone fusion at 6 months after surgery. Japanese Orthopaedic Association Back Pain Evaluation Questionnaire and Oswestry Disability Index results improved postoperatively in both groups. Conclusion: Using the TiPEEK cage for PLIF enabled the maintenance of better bone fusion to the endplate than using the PEEK cage at 6 months after the surgery. Our findings suggest the possibility of an earlier return to rigorous work or sports by the use of TiPEEK cage. Level of Evidence: 1 Abstract : We conducted a randomized controlled study of patients with single-level posterior lumbar interbody fusion (PLIF). Using the titanium-coated polyetheretherketone (TiPEEK) cage enabled the maintenance of better bone fusion than using the PEEK cage at 6 months after PLIF. We hope to obtain early bone fusion by using the TiPEEK cage.